Forward guidance with preferences over safe assets - Ansgar Rannenberg (National Bank of Belgium, 2019)
I develop a New Keynesian model with preferences over safe assets (POSA) calibrated using evidence on the wedge between household discount rates and market interest rates. POSA attenuate intertemporal consumption smoothing and thus the household's responsiveness to future interest rates, the more so the more distant in time they are located, and imply a consumption wealth effect. Therefore, POSA substantially lower the macroeconomic effect of forward guidance policies. By contrast, POSA does not substantially change the effect of the standard shocks of Smets/Wouters (2007) type DSGE models. The results carry over to a model with Iacoviello (2005,2014)-type collateral constraints. Such constraints in themselves tend to strongly amplify the effect of forward guidance.
Keywords: E52; E62; E32; 330; Forward guidance puzzle; preferences over safe assets; monetary policy; collateral constraints